Role of HbA1c in Prediction of Gestational Diabetes Mellitus Patients - Sema KARDEŞLER; Deniz İlhan TOPÇU; Mustafa TERZİOĞLU; Esin KASAP; Ayfer ÇOLAK (Forbes Tıp Dergisi, 2024)
Objective: Gestational diabetes mellitus (GDM) is observed in pregnant women worldwide with a prevalence ranging between 1% and 14%. The oral glucose tolerance test (OGTT) is performed for diagnosis. We compared the diagnostic value of HbA1c with the OGTT test in the diagnosis of GDM. Methods: 24-28 weeks pregnant women whose HbA1c was studied on the same day between 2019- 2023 January and who had OGTT with 75 g oral glucose were included in the study. Age, HbA1c, and hemoglobin values of groups separated as GDM and non-GDM were compared with the Wilcoxon test. Logistic regression analysis was used to determine the relationship of fasting plasma glucose (FPG) and HbA1c values with the OGTT result. Finally, ROC analysis was performed to evaluate diagnostic performance. Results: According to the OGTT results, out of 81 patients included in the study, 28 (34.6%) were classified as non-GDM, and 53 (65.4%) were classified as GDM. The median HbA1c value of the non-GDM group is 5.05% and the GDM group is 5.3%, and the statistical difference between the two groups is significant (p=0.032). In the ROC analysis, the AUC was 0.65 for HbA1c, 0.94 for FPG and 0.94 for HbA1c + FPG. Conclusion: In the prediction of GDM, the diagnostic performance of ROC analysis alone or even together with the FPG value of HbA1c is low; It has been observed that HbA1c is not sufficient for diagnosis in patients with suspected GDM and OGTT study may be more effective.